Optimal First-Line Use of Pembrolizumab in Metastatic Driver-Negative NSCLC: Monotherapy Versus Chemo-Immunotherapy (Evidence 2022–2025) - Bachurski, Patryk; Chmiel, Gabriela; Kalinowski, Paweł; Międlar, Maja; Muda, Martyna; Pacek, Szymon; Pierzga, Elisabetta; Wiśniewski, Karol; Witkowski, Paweł; Zarański, Bartosz (Quality in Sport, 2026)
Pembrolizumab has redefined first-line treatment of metastatic non-small cell lung cancer (NSCLC) without targetable driver alterations, both as monotherapy in PD-L1-high disease and in combination with platinum-based chemotherapy across PD-L1 strata. Since 2021, the strategic focus has shifted from whether to use pembrolizumab to how best to deploy it. This review summarizes evidence from 2022–2025, including randomized trial updates, pembrolizumab-specific network meta-analyses, real-world cohorts, and guideline recommendations. Across randomized and pooled analyses, pembrolizumab–chemotherapy improves objective response and progression-free survival compared with pembrolizumab monotherapy, particularly in PD-L1 tumor proportion score (TPS) 1–49% and <1% tumors. In PD-L1-high disease (TPS ≥50%), combination therapy achieves higher response rates and longer PFS but does not clearly improve overall survival compared with monotherapy after adjustment for cross-trial and real-world confounding. Real-world cohorts consistently show reduced early progression and early death with combination therapy, especially in patients with high tumor burden or aggressive disease, but only modest long-term survival benefit at the population level. Pembrolizumab monotherapy provides durable survival with lower acute toxicity, median overall survival of approximately 20–26 months, and a 5-year survival rate of 20–30% in PD-L1-high cohorts, with good tolerability even in older patients. Clinical and biological modifiers, including tumor burden, disease aggressiveness, neutrophil-to-lymphocyte ratio, histology, age, and performance status, refine patient selection beyond PD-L1 alone. Current guidelines therefore view pembrolizumab monotherapy and pembrolizumab–chemotherapy as complementary options supporting individualized treatment selection.